Pengaruh Keterampilan dan Karakteristik Kepribadian terhadap Kinerja Karyawan Pada PT Telkom Akses Sorong - Susetyowati Sofia; Sulistari; Digor Mufti (Journal of Economics and Management (JECMA), 2023)
This study uses 3 variables, namely skills and personality characteristics as independent variables, employee performance variables as the dependent variable. This study aims to determine the effect of skills on employee performance at PT Telkom Access Sorong, to determine the effect of personality characteristics on employee performance at PT Telkom Access Sorong, and to determine the effect of skills and personality characteristics on employee performance at PT Telkom Access Sorong. This research is a quantitative research using a correlation approach. The population in this study is the Technician Employees of PT Telkom Access Sorong which is limited to the operation division of the technician section. The sample of this study amounted to 49 people. The sampling technique of this study used non-probability sampling with saturated sampling technique. The results of this study are 1) skills affect employee performance at PT Telkom Access Sorong, 2) characteristics affect employee performance at PT Telkom Access Sorong, 3) skills and personality characteristics on employee performance at PT Telkom Access Sorong. In testing the hypothesis, the t-value of skills (X1) is 11.624, and the t-value of personality characteristics is 8.272, then simultaneous testing shows the f-count of 486.854 with a significance value of 0.00, so it can be concluded that skills and personality characteristics on performance employees at PT Telkom Access Sorong